Altering environmental conditions induce shifts in simulated deep terrestrial subsurface bacterial communities—Secretion of primary and secondary metabolites - Merja Herzig; Tuulia Hyötyläinen; Gianni F. Vettese; Gareth T. W. Law; Taavi Vierinen; Malin Bomberg (Environmental Microbiology, 2024)
The deep terrestrial subsurface (DTS) harbours a striking diversity of microorganisms. However, systematic research on microbial metabolism, and how varying groundwater composition affects the bacterial communities and metabolites in these environments is lacking. In this study, DTS groundwater bacterial consortia from two Fennoscandian Shield sites were enriched and studied. We found that the enriched communities from the two sites consisted of distinct bacterial taxa, and alterations in the growth medium composition induced changes in cell counts. The lack of an exogenous organic carbon source (ECS) caused a notable increase in lipid metabolism in one community, while in the other, carbon starvation resulted in low overall metabolism, suggesting a dormant state. ECS supplementation increased CO 2 production and SO 4 2− utilisation, suggesting activation of a dissimilatory sulphate reduction pathway and sulphate‐reducer‐dominated total metabolism. However, both communities shared common universal metabolic features, most probably involving pathways needed for the maintenance of cell homeostasis (e.g., mevalonic acid pathway). Collectively, our findings indicate that the most important metabolites related to microbial reactions under varying growth conditions in enriched DTS communities include, but are not limited to, those linked to cell homeostasis, osmoregulation, lipid biosynthesis and degradation, dissimilatory sulphate reduction and isoprenoid production.

Uranium(VI) interactions with Pseudomonas sp. PS-0-L, V4-5-SB and T5-6-I - Jenna Kasko; Xiaodong Li; Katharina Müller; Yanling Ge; Gianni F. Vettese; Gareth T.W. Law; Marja Siitari-Kauppi; Nina Huittinen; Johannes Raff; Malin Bomberg; Merja Herzig (Applied Geochemistry, 2023)